2018
DOI: 10.1186/s12992-018-0341-1
|View full text |Cite
|
Sign up to set email alerts
|

South-south collaboration on HIV/AIDS prevention and treatment research: when birds of a feather rarely flock together

Abstract: BackgroundSouth-south collaboration on health and development research is a critical mechanism for social and economic progress. It allows sharing and replicating experiences to find a “southern solution” to meet shared health challenges, such as access to adequate HIV/AIDS prevention and treatment. This study aimed to generate evidence on the dynamics of south-south collaboration in HIV/AIDS research, which could ultimately inform stakeholders on the progress and nature of collaboration towards increased rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 42 publications
(41 reference statements)
1
14
0
Order By: Relevance
“…An interesting finding from our analyses is that Africa-based researchers may more readily hold a prime authorship position if they engage in South-South collaborations with researchers from other African countries. Similar to others,35–38 we found that intra-African collaborations produced a small fraction of the health research in Africa, and of these, South African researchers were the most common collaborative partner 35 39. Beyond the benefit of local representation in first and last authorship positions, these collaborations likely focus on research priorities of the region 40.…”
Section: Discussionsupporting
confidence: 81%
“…An interesting finding from our analyses is that Africa-based researchers may more readily hold a prime authorship position if they engage in South-South collaborations with researchers from other African countries. Similar to others,35–38 we found that intra-African collaborations produced a small fraction of the health research in Africa, and of these, South African researchers were the most common collaborative partner 35 39. Beyond the benefit of local representation in first and last authorship positions, these collaborations likely focus on research priorities of the region 40.…”
Section: Discussionsupporting
confidence: 81%
“…Tackling these challenges and coming up with pragmatic solutions requires robust research [6,7]. This need for local research is occurring when Africa has in the recent past been reported to lag behind other regions in research output -producing less than 1% of the world's research [8], including research in the elds of population and health [9,10]. The under-performance in research in Africa is partly due to inadequate research funding by African governments [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Tackling these challenges and coming up with pragmatic solutions requires robust research [6,7]. This need for local research is occurring when Africa has in the recent past been reported to lag behind other regions in research output -producing less than 1% of the world's research [8], including research in the fields of population and health [9,10]. The under-performance in research in Africa is due in-part to inadequate research funding by African governments [11,12].…”
Section: Introductionmentioning
confidence: 99%